Spectrophotometric Determination of Promethazine in Pharmaceutical Preparations - Sh.H. Mohamad; Sh.L Al-Najafi; AM. Al-Abachi (College of Education for Pure Sciences, 2006)
A batch and flow injection (FIA) spectrophotometric methods have been developed for the determination of promethazine in aqueous solution and in pharmaceutical preparations. The methods are based on the reaction of promethazine with sulphanilic acid in the presence of N-bromosuccinimide as oxidizing agent. The water soluble bluish- green dye produced is measured at Xmax 600 nm, linearity is observed from 2-30 and from 2-100 p-gml"1 promethazine with detection limits of 0.20 and 0.43 ^ig ml"1 promethazine by batch and FIA procedures, respectively. The effect of chemical and physical parameters has been carefully considered and the proposed procedures have successfully been applied to the determination of promethazine in pharmaceutical formulations.